Evolutionarily Stable Preferences in Contests - Wolfgang Leininger (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2008)
We define an indirect evolutionary approach formally and apply it to (Tullock)contests. While it is known (Leininger, 2003) that the direct evolutionary approach in the form of finite population ESS (Schaffer, 1988) yields more aggressive behavior than in Nash equilibrium, it is now shown that the indirect evolutionary approach yields the same more aggressive behavior, too. This holds for any population size N, if evolution of preferences is determined by behavior in two-player contests. The evolutionarily stable preferences (ESP) of the indirect approach turn out to be negatively interdependent, thereby rationalizing the more aggressive behavior.
Keywords: C79; D72; 330; Rent Seeking; Wettbewerb; Evolutionäre Spieltheorie; Präferenztheorie; Theorie